2007
DOI: 10.5032/jae.2007.02056
|View full text |Cite
|
Sign up to set email alerts
|

The Instructional Planning Experiences Of Beginning Teachers

Abstract: The purpose of this collective case study was to understand the nature of planning and the influences on planning among intern and novice teachers in Illinois. Sixteen intern teachers and 15 novice teachers participated in reflections, focus group interviews, and individual interviews. In regard to the nature of planning, both intern and novice teachers planned as a mental process, conceptualized and prioritized content, and utilized a daily or hourly planning approach. Interns differed from novices in the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 13 publications
1
12
0
4
Order By: Relevance
“…Farrell (2014) made a similar point when he indicated that this type of reflection requires the teachers to anticipate what will occur during the lesson, as well as reflect on their past experiences before a lesson occurs. This type of reflection fits well with Ball et al (2007) description of the first step of teachers thought processes, which is thinking before the actual teaching takes place. This also signifies the importance of reflections on instructional planning.…”
Section: The Significancementioning
confidence: 88%
See 3 more Smart Citations
“…Farrell (2014) made a similar point when he indicated that this type of reflection requires the teachers to anticipate what will occur during the lesson, as well as reflect on their past experiences before a lesson occurs. This type of reflection fits well with Ball et al (2007) description of the first step of teachers thought processes, which is thinking before the actual teaching takes place. This also signifies the importance of reflections on instructional planning.…”
Section: The Significancementioning
confidence: 88%
“…Schon (1983) attributed this kind of reflection as reflection-in-action. Akbari (2007) and Ball, Knobloch and Hoop (2007) noted that this kind of reflection as "online reflection" that practitioners or teachers will encounter during their teaching actions; which may be difficult to be executed by some practitioners due to the demanding nature of thinking-on-your-feet. In Farrell (2014), reflection-in-action is described as a more immediate type of reflection; where teachers will have to make decisions on spontaneous, in-class incidents, for example, on students' response to the activity.…”
Section: Reflective Practicementioning
confidence: 99%
See 2 more Smart Citations
“…Ball, Knobloch, and Hoop (2007) explain that instructional planning is essential to teaching because it is the process by which teachers link the curriculum to learning. In the present study, beginning teachers engaged in diverse means of planning reading instruction that included utilizing district resources as well as planning that extended beyond the designated time during the school day.…”
Section: Instructional Planning For Teaching Readingmentioning
confidence: 99%